Some geometric properties of the metric space [InlineEquation not available: See fulltext.] Recent Trends on Inequalities and its Applications - Çinar, M.; Karakaş, M.; Et, Mikail (My University, 2013)
In this study, we consider the space [InlineEquation not available: see fulltext.] with an invariant metric. Then, we examine some geometric properties of the linear metric space [InlineEquation not available: see fulltext.] such as property (?), property (H) and k-NUC property. MSC: 40A05, 46A45, 46B20. © 2013 Çinar et al.; licensee Springer.
Keywords: de la Vallée-Poussin mean; k-NUC property; linear metric space; Luxemburg norm; property (H)